Exploring the Connection between Adult Playfulness and Emotional Intelligence - Robyn Holmes; Tori Hart (University of Huddersfield Press, 2022)
This study explored the connection between adult playfulness and emotional intelligence. Participants were 325 (39 men, 286 women) primarily European American, (59%), undergraduate students attending a private, four year, liberal arts university in the northeastern United States. Participants completed two standard measures - The Schutte Self Report Emotional Intelligence Test (SSEIT) and The Adult Playfulness Trait Scale (APTS). In addition, participants completed an open ended query - "How do you define play?" to complement the correlation analyses. Correlational analyses revealed strong, positive connections between the SSEIT and APTS subscale and total scores. The Fun Seeking subscale of the APTS positively connected to all subscales of the SSEIT. Engaging in fun and having a good time was a playfulness component and temperamental disposition that helps one perceive, manage, and utilize emotions as well as manage the emotions of social others. The Uninhibited subscale of the APTS connected positively to two of the SSEIT subscales - Managing one's emotions and Utilizing emotions. Finally, individuals who scored high on the APTS also scored high on the SSEIT. This study's findings suggest that the temperamental disposition, playfulness connects to an individual's emotional intelligence. Future studies might investigate different cultural and age groups and utilize mixed method approaches to broaden our understanding of how playfulness helps people process emotional experience related to the self and social others.